Antiresonant guiding in a poly(methyl-methacrylate) hollow-core optical fiber. (21st August 2015) - Markos, Christos; Nielsen, Kristian; Bang, Ole
Abstract: Strong antiresonant reflecting optical waveguiding is demonstrated in a novel poly (methyl-methacrylate) (PMMA) hollow-core fiber. The transmission spectrum of the fiber was characterized using a supercontinuum source and it revealed distinct resonances with resonant dips as strong as ∼20 dB in the wavelength range 480–900 nm, where PMMA has low absorption. The total propagation loss of the fiber was measured to have a minimum of ∼45 dB m −1 at around 500 nm. The thermal sensitivity of the fiber is 256 ± 16 pm °C −1, defined as the red-shift of the resonances per °C, which is three times higher than the sensitivity of polymer fiber Bragg gratings.